Examining the role of lymphocytes in health and in neonatal encephalopathy and the influence of mucosal associated T cells on B cell functions - Taher, Nawal Abdulla Abdullah (Trinity College Dublin. School of Medicine. Discipline of Immunology, 2022)
Background. Neonatal encephalopathy (NE) is a neurological syndrome in term babies characterised by altered levels of consciousness, seizures, abnormal tone and reflexes, and/or failure to initiate or maintain respiration. NE affects 1.15 million babies every year worldwide. It carries a postnatal mortality of 28% and a third of surviving infants exhibit permanent neurodevelopmental delay in the form of cerebral palsy (CP), cognitive disabilities, or epilepsy. The only treatment available is therapeutic hypothermia, however, this is effective only in a proportion of patients. Therefore, there is an urgent need to discover new therapies for NE. Inflammation plays a major role in brain injury associated with NE. It is characterised by astrocyte and microglial cell activation and the release of inflammatory cytokines which result in the recruitment of neutrophils and monocytes to the brain. While effector cells of the innate immune system clearly contribute to the pathogenesis of NE, little is known about the role of lymphocytes, the central controllers of innate and adaptive immune responses. Methods. We used flow cytometry to profile the frequencies of conventional T cells, B cells and natural killer (NK) cells, and subpopulations of innate T cells in 10 cord blood samples and peripheral blood samples from 17 healthy neonates, 23 school-aged children, 25 young adults and 10 older adults to examine age-related changes in lymphocyte numbers and phenotypes. We also investigated if circulating lymphocyte numbers and functions are altered in 30 neonates with NE, 10 school-age children with a history of NE and 10 children with CP. Finally, we investigated if mucosal associated invariant T (MAIT) cells, whose numbers are reduced in NE patients, are capable of activating B cells in co-culture experiments, to determine if MAIT cells can contribute to humoral immunity. Results. The frequencies of total, CD4+ and CD8+ T cells remained relatively constant in healthy donors throughout life. B cells expanded after birth and reached peak levels at school age and then decreased gradually throughout adulthood. NK cell numbers were low in cord blood and in neonatal blood, but they steadily expanded throughout adulthood. Analysis of four innate T cell populations – Vδ1+ and Vδ2+ γδ T cells, MAIT cells and invariant natural killer T (iNKT) cells – revealed that all of these cell types are found at very low frequencies in cord blood and in peripheral blood of neonates, but they expand after birth and throughout childhood and adulthood. Compared to neonates and children, adults had higher serum levels of proinflammatory and T helper type 1 (Th1) cytokines but normal levels of Th2 and Th17 cytokines. Analysis of patients with NE indicated that B cell frequencies and numbers were significantly higher in neonates and school-age children with NE compared to healthy age-matched children. The numbers and frequencies of total T cells were higher in children with CP but similar in the other subject groups. Analysis of CD4 and CD8 expression by these T cells revealed that CD4+ and CD8+ T cell frequencies were similar in patients and controls, but CD4−CD8− and CD4+CD8+ T cells were present in greater numbers in school-age children who had NE compared to healthy school-age children. iNKT cell and Vδ2 T cell numbers and frequencies were strikingly higher in neonates with NE, children post-NE and children with CP compared to age-matched controls, whereas MAIT cells and Vδ1 T cells were depleted from children with cerebral palsy. Upon stimulation ex vivo, T cells, NK cells and Vδ2 T cells from neonates with NE more readily produced inflammatory cytokines than their counterparts from healthy neonates, suggesting that they were previously primed or activated. In the final results chapter, we investigated if MAIT cells can induce B cell activation and maturation. Upon co-culture with expanded MAIT cells, B cells upregulated cell-surface markers of antigen presenting cells, secreted cytokines, underwent immunoglobulin class-switching and released antibodies. We also found that MAIT cells can kill B cells. Conclusions. The results of this study show that T, B and NK cell frequencies fluctuate with age, and are likely to lead to age-related changes in immunocompetence which can contribute to susceptibility to infection in infants and inflammaging and immunosenescence in older people. Innate and conventional lymphocytes, in particular Vδ2 T cells and iNKT cells, are also numerically and functionally altered in neonates with NE and these changes may persist into school age. MAIT cells are capable of inducing B cell maturation and antibody production. Further research is required to determine if innate T cells can be targeted for the prevention or treatment of NE or CP.
APPROVED
Keywords: immunology